1000MPa-grade hydrogen-induced delayed cracking-resistant plating-free hot forming steel and preparation method thereof

By adjusting the alloy elements and process flow, a 1000MPa-grade hydrogen-induced delayed cracking-free coating hot-formed steel was designed, which solved the oxidation and decarbonization problems of hot-formed steel during hot stamping forming, and improved the resistance to hydrogen-induced delayed cracking and High temperature oxidation resistance simplifies the preparation process and improves production efficiency.

CN119121072APending Publication Date: 2024-12-13PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324999.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing 1000MPa grade hot-formed steel has serious oxidation and decarbonization problems during the hot stamping process, resulting in reduced dimensional accuracy of stamping parts, low industrial production efficiency, and poor resistance to hydrogen-induced delayed cracking.

Method used

By adjusting the addition and content of alloy elements, a 1000MPa-grade hydrogen-induced delayed cracking-free coating hot-formed steel was designed, using a double-roll thin-band continuous casting process and a one-time hot rolling + coiling process, combining pickling and EPS production line treatment. Remove the iron oxide sheet, control the water temperature and superheat of the steel to form a thermoformed steel with good high-temperature oxidation resistance and high bending toughness.

Benefits of technology

The high-temperature oxidation resistance and hydrogen-induced delayed cracking resistance of 1000MPa grade thermoformed steel has been improved, which simplifies the preparation process, reduces energy consumption and carbon emissions, avoids shot peening, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides 1000 MPa grade hydrogen induced delayed cracking resistant plating-free hot forming steel which comprises the following components in percentage by mass: 0.06%-0.08% of C, 0.5%-1.0% of Mn, 0.3%-1.5% of Si, 0.08%-0.25% of Al, 0.012%-0.028% of Ti, 0.03%-0.25% of (Nb + V + Mo), 1.5%-3.0% of Cr, 0.005%-0.05% of (La + Ce), 0.0035%-0.0081% of N and the balance of Fe. The invention further provides a preparation method of the hot forming steel. According to the hot forming steel provided by the invention, through element selection and content control, the hot forming steel has good high-temperature oxidation resistance, relatively high bending toughness and relatively good hydrogen-induced delayed cracking resistance; and the preparation process of the hot-formed steel is short in flow, efficient and green.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of steel preparation, and in particular to a 1000MPa-grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel and a preparation method thereof. Background Art

[0002] Hot-formed steel is an important lightweight material for body-in-white. Compared with cold stamping technology, hot stamping technology has the technical advantages of low springback, high forming ability, low stamping load and long mold service life.

[0003] During a car collision, hot-formed steel can be divided into anti-intrusion hot-formed steel and high-energy-absorbing hot-formed steel according to its role in the body-in-white. Among them, the yield strength and tensile strength of anti-intrusion hot-formed steel are usually higher. 22MnB5 steel is a typical anti-intrusion hot-formed steel, and its yield strength and tensile strength reach 1100MPa and 1500MPa respectively, but its toughness is poor. On the contrary, high-energy-absorbing hot-formed steel has higher toughness and absorbs the energy brought by the collision through good deformation ability during deformation. Low-carbon martensitic hot-formed steel with a tensile strength of 1000MPa is a typical high-energy-absorbing hot-formed steel. However, for 1000MPa-level hot-formed steel bare plates, they face serious oxidation and decarburization problems during the hot stamping process. The stamped parts need to be shot peened to remove the oxide scale, which leads to a decrease in the dimensional accuracy of the stamped parts, and the iron oxide scale that falls off in the mold needs to be cleaned in time, thereby reducing the industrial production efficiency of the stamped parts. At present, the high temperature oxidation and decarburization problems of hot-formed steel can be solved by Al-Si coating technology, but its manufacturing cost is high, and commercial production is limited by patent blockade. Therefore, it is urgent to develop 1000MPa-level coating-free hot-formed steel; in addition, delayed cracking resistance is an important performance indicator of hot-formed steel, that is, 1000MPa-level coating-free hot-formed steel should also have good resistance to hydrogen-induced delayed cracking.

[0004] The Chinese patent with publication number CN117265225A relates to a coating-free hot-formed steel and its preparation method, which includes the following raw materials in mass percentage: C: 0.3%~0.45%, Si: 0.8%~1.5%, Mn: 1.2%~2.5%, Cr: 0.8%~2.4%, Ti: 0.01%~0.02%, B: ≤0.002%, Ni: 0.05%~0.15%, Mo: ≤0.3%, Nb: 0.04~0.1%, Al: 0.05~0.20%, P, S: ≤0.02%, and the rest are Fe and unavoidable impurity elements. It can be seen from the composition of this steel that it contains high C and Mn content, which will inevitably lead to poor indicators such as weldability and bending fracture strain, and its resistance to hydrogen-induced delayed cracking is correspondingly poor.

[0005] In addition, the existing 1000MPa low-carbon martensitic hot-formed steel bare plate usually needs to be prepared through a complex production process, including: smelting molten steel → thick slab continuous casting → slab cutting → slab high temperature heating and insulation → dephosphorization → rough rolling → finishing rolling → laminar cooling → coiling → pickling → cold rolling → continuous annealing. This production process has high carbon emissions, long production lines, and high energy consumption. Summary of the invention

[0006] The technical problem solved by the present invention is to provide a 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel. The hot-formed steel provided by the present application has good high-temperature oxidation resistance, high bending toughness and good hydrogen-induced delayed cracking resistance.

[0007] In view of this, the present application provides a 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel, which includes, by mass percentage: C 0.06~0.08%, Mn 0.5%~1.0%, Si 0.3%~1.5%, Al 0.08%~0.25%, Ti 0.012%~0.028%, (Nb+V+Mo) 0.03%~0.25%, Cr 1.5%~3.0%, (La+Ce) 0.005%~0.05%, N 0.0035%~0.0081%, P≤0.0075%, O<0.0025%, and Mn+Si≤2.0%, 0.4%≤Al+Si≤1.6%, 1.8%≤Si+Cr≤3.3%, and the rest is Fe.

[0008] Preferably, the Mn content is 0.7-0.9%.

[0009] Preferably, the content of Mn+Si is 1.3%~1.7%.

[0010] Preferably, 0.8%≤Al+Si≤1.5%.

[0011] Preferably, the Si content is 0.5~1.2%, the Al content is 0.09~0.20%, the Ti content is 0.02~0.026%, (Nb+V+Mo) 0.05%~0.20%, Cr 2.0%~2.8%, (La+Ce) 0.010%~0.025%, N 0.0038%~0.0058%, and 2.0%≤Si+Cr≤3.0%.

[0012] The present application also provides a method for preparing the hot-formed steel, comprising the following steps:

[0013] S1) preparing the raw materials according to the composition ratio, smelting the obtained mixed raw materials to obtain molten steel; during the smelting process, a magnesium-based alloy is used for deoxidation, and the magnesium-based alloy includes 50-60wt% Mg, 20-25wt% Al, 15-20wt% Ca, and 2.3-3.6wt% Ba;

[0014] S2) pouring the molten steel into a tundish and a flow ladle in sequence and then into a twin-roller thin strip continuous casting device for continuous casting to obtain a cast strip;

[0015] S3) cooling the cast strip and then hot rolling it once, laminar cooling the obtained hot-rolled plate and then coiling it to obtain a coiled hot-rolled plate;

[0016] S4) removing the iron oxide scale from the coiled hot-rolled sheet and then hot stamping the sheet to obtain 1000 MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel.

[0017] Preferably, in step S1), the magnesium-based alloy is added in the form of iron cored wire, the addition timing is 28-32 seconds after the molten steel is tapped, and the amount of the iron cored wire added is 3.3-3.5 kg / t;

[0018] In step S2), the temperature of the molten steel is 1612-1620°C; the superheat of the molten steel in the tundish is 50-70°C, the superheat of the molten steel on the upper surface of the molten pool between the casting rollers in the twin-roll thin strip continuous casting equipment is 10-40°C, the continuous casting is carried out under a protective atmosphere, the thickness of the cast strip is 1.9-2.1 mm, and the width is 1-1.2 m.

[0019] Preferably, in step S3), the starting rolling temperature of the hot rolling is 1000-1050°C, the finishing rolling temperature is 920-950°C, the thickness of the hot-rolled plate is 1.0-1.7 mm; the cooling rate of the laminar cooling is 10-15°C / s, and the temperature is 560-620°C; the oxide layer thickness of the hot-rolled plate after coiling is 5-9 μm;

[0020] In step S4), the method of removing the iron oxide scale is selected from one or both of pickling treatment and EPS production line treatment; the pickling passes through three pickling tanks in sequence, the acid concentrations are 30-40g / L, 50-60g / L, and 80-90g / L respectively, the pickling temperature is 60-70°C, and the pickling speed is 60-80m / min; the EPS production line treatment is carried out using recycled harmless medium water and steel grit.

[0021] Preferably, in step S4), the hot stamping is specifically:

[0022] The hot rolled plate after removing the iron oxide scale is heated to 900-930°C in a heating furnace, and the total time = (the thickness of the hot rolled plate after removing the iron oxide scale * 100 + 70-90) s, and then transferred to the mold in 5-10s and quenched to 100-200°C, the pressure is 10-20MPa, and the pressure is maintained for 5-15s; the atmosphere of the heating furnace is dry compressed air, nitrogen or argon, and the dew point is -30--5°C;

[0023] The oxide layer thickness of the 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel is 10-30nm.

[0024] Preferably, the hot stamping further includes tempering, and the tempering temperature is 150-200° C. and the time is 10-30 min.

[0025] The present application provides a 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel, which comprises: C 0.06%~0.08%, Mn 0.5%~1.0%, Si 0.3%~1.5%, Al 0.08%~0.25%, Ti 0.012%~0.028%, (Nb+V+Mo) 0.03%~0.25%, Cr 1.5%~3.0%, (La+Ce) 0.005%~0.05%, N 0.0035%~0.0081%, P≤0.0075%, O<0.0025%, and Mn+Si≤2.0%, 0.4%≤Al+Si≤1.6%, 1.8%≤Si+Cr≤3.3%, and the rest is Fe; in hot-formed steel, by adding Al, Si, Cr, (La+Ce) elements and controlling their content, the oxidation resistance of hot-formed steel is improved, so that hot-formed steel does not need nitrogen or inert gas protection during hot stamping, and stamping parts do not need shot peening; Strictly limiting the contents of O, Mn, Si, Al and Cr can slow down the high-temperature oxidation of hot-rolled plates and reduce the thickness of the oxide layer of hot-rolled plates after coiling. At the same time, the addition of one or more of Nb, V and Mo is conducive to the formation of micro-alloy carbides as hydrogen traps, and can also regulate the temperature of the martensitic phase transformation point Ms, so that sufficient ε / η carbides can be obtained as hydrogen traps after quenching + tempering treatment; at the same time, limiting the P content to ≤0.0075% can reduce the segregation of P at the grain boundary and further improve the resistance to hydrogen-induced delayed cracking.

[0026] Furthermore, the present application also provides a method for preparing 1000MPa-grade hydrogen-induced delayed cracking-resistant uncoated hot-formed steel, which introduces a twin-roll thin-strip continuous casting process and combines it with a single hot rolling and coiling process, so that the hot-formed steel preparation process is short and the energy consumption is low. DETAILED DESCRIPTION

[0027] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0028] In view of the fact that existing 1000MPa-grade low-carbon martensitic hot-formed steel bare plates are prone to severe high-temperature oxidation and decarburization during the hot stamping process, and that existing industrial production lines have high carbon emissions, high energy consumption, and long production lines, the present application provides a 1000MPa-grade hydrogen-induced delayed cracking resistant and coating-free hot-formed steel, which, by designing the addition of alloy elements and adjusting the content, has good high-temperature oxidation resistance, high bending toughness and good resistance to hydrogen-induced delayed cracking. Furthermore, the present application also provides a method for preparing hot-formed steel, which introduces a twin-roll thin strip continuous casting process to prepare hot-formed steel cast strips, thereby eliminating some of the steps in the conventional preparation process, making the preparation process short and efficient. Specifically, an embodiment of the present invention discloses a 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel, which includes, by mass percentage: C 0.06~0.08%, Mn 0.5%~1.0%, Si 0.3%~1.5%, Al 0.08%~0.25%, Ti 0.012%~0.028%, (Nb+V+Mo) 0.03%~0.25%, Cr 1.5%~3.0%, (La+Ce) 0.005%~0.05%, N 0.0035%~0.0081%, P≤0.0075%, O<0.0025%, and Mn+Si≤2.0%, 0.4%≤Al+Si≤1.6%, 1.8%≤Si+Cr≤3.3%, and the rest is Fe.

[0029] In the 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel provided in the present application, the C content is 0.06-0.08%, specifically, the C content is 0.06%, 0.07% or 0.08%.

[0030] The content of Mn is 0.5-1.0%. Specifically, the content of Mn is 0.7-0.9%. For example, the content of Mn in the present application is 0.6% and 0.8%.

[0031] The Cr content is 1.5~3.0%, specifically, the Cr content is 2.0~2.8%; for example, the Cr content in this application is 1.6%, 1.7%, 1.8%, 1.9%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, and 2.9%.

[0032] The present application regulates the content of Mn and Cr to ensure that the 1000MPa grade hot-formed steel has good hardenability and that the structure after hot stamping and quenching is martensite + bainite + microalloy carbide + ε / η carbide.

[0033] The Si content is 0.3-1.5%, specifically, the Si content is 0.5-1.2%; for example, the Si content in this application is 0.4%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.3%, and 1.4%.

[0034] Further, Mn+Si≤2.0%, specifically, 1.3%≤Mn+Si≤1.7%; by way of example, the content of Mn+Si in this application is 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.8%, and 1.9%.

[0035] The Al content is 0.08-0.25%, specifically, the Al content is 0.09-0.20%; for example, the Al content in this application is 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.21%, 0.22%, 0.23%, and 0.24%.

[0036] Further, 0.4%≤Al+Si≤1.6%, specifically, 0.55%≤Al+Si≤1.5%; by way of example, the Al+Si content in this application is 0.45%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.08%, 1.1%, 1.2%, 1.3%, and 1.4%.

[0037] The present application also limits the content of O, O<0.0025%; the limits of the contents of O, Mn, Si, Al and Cr in the present application can slow down the degree of high-temperature oxidation of the hot-rolled plate and reduce the thickness of the oxide layer of the hot-rolled plate after coiling.

[0038] Further, 1.8%≤Si+Cr≤3.3%, specifically, the content of Si+Cr is 2.0~3.0%; for example, the content of Si+Cr in this application is 1.9%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 2.9%, 3.1%, and 3.2%.

[0039] The Ti content is 0.012-0.028%, specifically, the Ti content is 0.02-0.026%; for example, the Ti content in this application is 0.013%, 0.014%, 0.015%, 0.016%, 0.017%, 0.018%, 0.019%, 0.021%, 0.022%, 0.023%, 0.024%, 0.025%, and 0.027%.

[0040] The N content is 0.0035-0.0081%, specifically, the N content is 0.0038-0.0058%; for example, the N content in the present application is 0.0036%, 0.0037%, 0.0039%, 0.0041%, 0.0042%, 0.0043%, 0.0045%, 0.0044%, 0.0046%, 0.0047%, 0.0048%, 0.0049%, 0.0050%, 0.0051%, 0.0052%, 0.0053%, 0.0054%, 0. 0.0055%, 0.0056%, 0.0057%, 0.0059%, 0.0060%, 0.0061%, 0.0062%, 0.0063%, 0.0064%, 0.0065%, 0.0066%, 0.0067%, 0.0068%, 0.0069%, 0.0070%, 0.0071%, 0.0072%, 0.0073%, 0.0074%, 0.0075%, 0.0076%, 0.0077%, 0.0078%, 0.0079%, 0.0080%.

[0041] La and Ce, as rare earth elements, can deeply reduce the harmful effects of low melting point elements such as S and P. At the same time, trace amounts of rare earth elements can also improve the high temperature oxidation resistance of the material. However, if too much La+Ce is added, the nozzle will be blocked during the continuous casting process. The content of La+Ce is 0.005~0.05%, specifically, the content of La+Ce is 0.010~0.025%, and more specifically, the content of La+Ce is 0.012~0.022%.

[0042] In the present application, one or more of Nb, V and Mo are also added, that is, Nb, V and Mo can be added in one of the three, two of the three, or all three at the same time; the total addition amount of (Nb+V+Mo) is 0.03-0.25%, specifically, the total addition amount of (Nb+V+Mo) is 0.05-0.20%; for example, the total addition amount of (Nb+V+Mo) is 0.04%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.21%, 0.22%, 0.23%, 0.24%. In a specific embodiment, Nb and V are added at the same time, or Nb and Mo are added at the same time, or Nb is added. In the present application, one or more of Nb, V and Mo are added to form microalloy carbides as hydrogen traps; the martensitic phase transformation point Ms temperature is regulated by alloying elements so that sufficient ε / η carbides can be obtained as hydrogen traps after in-mold quenching + tempering treatment.

[0043] Furthermore, the present application also limits the P content, P≤0.0075%, to reduce P segregation at grain boundaries and further improve the resistance to hydrogen-induced delayed cracking.

[0044] The present application also provides a method for preparing hot-formed steel, comprising the following steps:

[0045] S1) preparing the raw materials according to the composition ratio, smelting the obtained mixed raw materials to obtain molten steel; during the smelting process, a magnesium-based alloy is used for deoxidation, and the magnesium-based alloy includes 50-60wt% Mg, 20-25wt% Al, 15-20wt% Ca, and 2.3-3.6wt% Ba;

[0046] S2) pouring the molten steel into a tundish and a flow ladle in sequence and then into a twin-roller thin strip continuous casting device for continuous casting to obtain a cast strip;

[0047] S3) cooling the cast strip and then hot rolling it once, laminar cooling the obtained hot-rolled plate and then coiling it to obtain a coiled hot-rolled plate;

[0048] S4) removing the iron oxide scale from the coiled hot-rolled sheet and then hot stamping the sheet to obtain 1000 MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel.

[0049] In the process of preparation, the present application firstly performs smelting, and in the process of smelting, a low-Ca+low-Al magnesium-based composite deoxidizing alloy is used for steelmaking deoxidation to avoid the formation of clustered or strip-shaped aluminum oxide after steelmaking Al deoxidation, thereby improving the quality of molten steel, and at the same time, avoiding the problem of easy plugging of water outlets. The magnesium-based composite deoxidizing alloy includes 50~60wt% Mg, 20~25wt% Al, 15~20wt% Ca, and 2.3~3.6wt% Ba. Specifically, the magnesium-based composite deoxidizing alloy includes 52.7~57wt% Mg, 21~23wt% Al, 16.4~19wt% Ca, and 2.5~3wt% Ba. The magnesium-based composite deoxidizing alloy described in the present application is first prepared into alloy particles with a particle size of 70-80 mm, and then made into iron cored wire (the skin is iron, and the core is magnesium-based composite deoxidizing alloy) through a cored operation. After the steel tapping is completed, the cored wire is added to the molten steel through a wire feeding machine; the cored wire is added 25-35 seconds after the molten steel is tapped, and the amount of the iron cored wire added is 3.0-4.0 kg / t.

[0050] The present application then pours the molten steel into the tundish, then flows from the tundish into the cloth ladle, and finally flows from the cloth ladle into the twin-roll thin strip continuous casting equipment for continuous casting to obtain a cast strip; the temperature of the molten steel is 1612~1620℃, specifically, the temperature of the molten steel is 1615~1618℃; the superheat of the molten steel in the tundish is 50~70℃, specifically, the superheat of the molten steel in the tundish is 60~68℃; the superheat of the molten steel on the upper surface of the molten pool between the casting rollers in the twin-roll thin strip continuous casting equipment is 10~40℃, specifically, the superheat of the molten steel on the upper surface of the molten pool between the casting rollers in the twin-roll thin strip continuous casting equipment is 20~30℃; the continuous casting is carried out under a protective atmosphere, and the thickness of the cast strip is 1.9~2.1mm and the width is 1~1.2m. The present application strictly controls the temperature and superheat of the molten steel in the above process, and can obtain a cast strip with good quality by continuous casting under a nitrogen protective atmosphere.

[0051] The above-mentioned twin-roll thin strip continuous casting is a potential low-carbon preparation process for producing low-strength, high-toughness hot-formed steel bare plates. Through the twin-roll thin strip continuous casting technology, liquid steel can be directly cast into two casting rolls rotating in opposite directions, and directly solidified and formed between the roll gaps of the casting rolls to prepare 1.9~2.1mm thin strip steel. This can eliminate the complex processes of thick slab continuous casting, ingot cutting, ingot high-temperature heating, dephosphorization, rough rolling, and finish rolling in the traditional hot-rolled strip steel production process, and has technical advantages such as low energy consumption, low carbon emissions, short production lines, and low investment costs.

[0052] The present application then cools the cast strip and then performs a hot rolling, and then coils the obtained hot-rolled plate after laminar cooling to obtain the coiled hot-rolled plate; the starting rolling temperature of the hot rolling is 1000~1050℃, the final rolling temperature is 920~950℃, and the thickness of the hot-rolled plate is 1.0~1.7mm, specifically, the starting rolling temperature of the hot rolling is 1020~1040℃, and the final rolling temperature is 930~940℃; the cooling rate of the laminar cooling is 10~15℃ / s, and the temperature is 560~620℃, specifically, the cooling rate of the laminar cooling is 11~13℃ / s, and the temperature is 580~600℃; the oxide layer thickness of the coiled hot-rolled plate is 5~9μm.

[0053] After the hot-rolled plate is coiled, there is iron oxide scale, i.e., an oxide layer, on its surface. The present application requires removing the oxide layer; the method for removing the oxide layer is selected from one or both of pickling and EPS production line treatment, and the pickling passes through three pickling tanks in sequence, and the acid concentrations are 30-40 g / L, 50-60 g / L, and 80-90 g / L, respectively. The pickling temperature is 60-70°C, and the pickling speed is 60-80 m / min; specifically, the pickling concentrations are 35-38 g / L, 55-58 g / L, and 85-88 g / L, respectively, the pickling temperature is 65-68°C, and the pickling speed is 70-78 m / min. During the pickling process, as the pickling progresses, the acid concentration in the acid tank increases successively, which can achieve different degrees of destruction of the oxide layer. Among them, the outermost oxide layer is easy to pickle away, and a lower concentration of acid is used. Then the acid concentration is increased successively to better remove the iron oxide layer from the outside to the inside. In this way, the efficiency of removing the iron oxide scale is better and more effective, and the disadvantage of unclean pickling of local areas of hot-rolled coils in a single acid tank can be avoided. After pickling, the EPS production line can be used for treatment according to the residual iron oxide scale to further remove the surface oxide scale and achieve rust prevention; the EPS production line treatment uses recycled harmless medium water and steel sand to remove the surface oxide scale and achieve rust prevention. In the process of removing the oxide layer in this application, pickling treatment is first used and then EPS production line treatment is used.

[0054] The microstructure of the hot-rolled plate after coiling consists of ferrite, martensite and bainite, wherein the volume fraction of ferrite is 50% to 55%, the volume fraction of martensite is 15% to 30%, and the volume fraction of bainite is 15% to 35%, and the yield strength of the hot-rolled plate after coiling is 500 to 530 MPa, the tensile strength is 660 to 690 MPa, and the total elongation is 18% to 25%.

[0055] According to the present invention, hot stamping is finally performed, and the hot stamping is specifically as follows:

[0056] The hot rolled plate after removing the iron oxide scale is heated to 900~930℃ in a heating furnace, and the total time = (thickness of the hot rolled plate after removing the iron oxide scale*100+70~90)s, and then transferred to the mold in 5~10s and quenched to 100~200℃, the pressure is 10~20MPa, and the pressure is maintained for 5~15s; the atmosphere of the heating furnace is dry compressed air, argon or nitrogen. The hot stamping in this application is heated in dry compressed gas without oxidation, and the dew point is -30~-5℃; the oxide layer thickness of the 1000MPa-level coating-free hot-formed steel is 10~30nm.

[0057] More specifically, the hot-rolled plate after removing the iron oxide scale is heated to 910~920°C in a heating furnace, and the total time = (thickness of the hot-rolled plate after removing the iron oxide scale*100+80~85)s, and then transferred to the mold in 6~8s and quenched to 120~150°C, the pressure is 15~18MPa, and the pressure is maintained for 6~10s; the dew point of the heating furnace is -20~-10°C; the oxide layer thickness of the 1000MPa-grade uncoated hot-formed steel is 12~20nm.

[0058] The microstructure of the oxidation-resistant hot-formed steel obtained after quenching in the hot stamping die is martensite + bainite + microalloy carbide + ε / η carbide, wherein the volume fraction of martensite is 65% ~ 95%, the volume fraction of bainite is 2% ~ 30%, the volume fraction of microalloy carbide is 0.2% ~ 0.5%, and the volume fraction of ε / η carbide is 2.8% ~ 5%; the tensile strength is 1000 ~ 1200MPa, the yield strength is 750 ~ 980MPa, the total elongation is 8% ~ 11%, and the corresponding bending angle under the maximum load of VDA238-100 three-point bending is 100 ° ~ 130 ° (the thickness of the sheet is 1.4mm).

[0059] Furthermore, the present application also performs a baking and coating treatment after hot stamping, that is, the hot deformed steel after hot stamping is tempered, and the tempering temperature is 150~200℃, and the time is 10~30min. Specifically, the tempering temperature is 170~190℃, and the time is 20~25min. The microstructure of the hot deformed steel after tempering is martensite+bainite+microalloy carbide+ε / η carbide, wherein the volume fraction of martensite is 64%~94%, the volume fraction of bainite is 1%~29%, the volume fraction of microalloy carbide is 0.1%~0.4%, and the volume fraction of ε / η carbide is 4.9%~7%; the tensile strength is 920~1180MPa, the yield strength is 870~1000MPa, the total elongation is 10%~13%, and the bending angle corresponding to the maximum load of VDA238-100 three-point bending is 110~140° (for a sheet with a thickness of 1.4mm); in a four-point bending hydrogen embrittlement test, no fracture occurs in HCl with a pH of 1 for 600h.

[0060] The present application provides a 1000MPa hydrogen-induced delayed cracking resistant coating-free hot-formed steel, which improves the oxidation resistance of the hot-formed steel by adding Al+Si+Cr+RE elements. During the hot stamping forming process, no nitrogen or inert gas protection is required in the heating furnace, and the stamping parts do not need shot peening. The mass percentages of O, Mn, Si, Al and Cr in the molten steel are strictly controlled to meet O<0.0025%, Mn+Si≤2.0%, 0.4%≤Al+Si≤1.6%, 1.8%≤Si+Cr≤3.3%, which can slow down the high-temperature oxidation degree of the hot-rolled plate and achieve the oxide layer thickness of the hot-rolled plate after coiling. The degree is 5~9μm; the Mn and Cr contents are further regulated to ensure that the 1000MPa grade hot-formed steel has good hardenability, so that the structure after hot stamping and quenching is martensite + bainite + microalloy carbide + ε / η carbide; one or more alloying elements such as Nb, V, and Mo are added to use microalloy carbides as hydrogen traps; the martensitic phase transformation point Ms temperature is regulated so that the 1000MPa grade hot-formed steel after in-mold quenching + baking and coating treatment obtains sufficient ε / η carbides as hydrogen traps; the P content is limited to less than 0.0075% to reduce the segregation of P at the grain boundary and further improve the resistance to hydrogen-induced delayed cracking.

[0061] The preparation method of 1000MPa hydrogen-induced delayed cracking resistant coating-free hot-formed steel provided in the present application strictly controls the mass percentage of the chemical composition of the deoxidized alloy, the temperature of the molten steel in the ladle, the superheat of the molten steel in the tundish, and the superheat of the molten steel on the upper surface of the molten pool between the casting rollers. Under the condition of nitrogen protective atmosphere, a cast strip with a thickness of 1.9~2.1mm and a width of 1~1.2m can be obtained by casting and rolling; and the oxide layer thickness of the hot-rolled plate after coiling prepared by double-roll thin strip continuous casting + one-pass hot rolling + coiling process is 5~9μm, and the oxide layer is easily removed by pickling with hydrochloric acid solution; the blank before hot stamping is prepared by double-roll thin strip continuous casting + one-pass hot rolling + coiling process, which has technical advantages such as low energy consumption, short production line, and low carbon emissions.

[0062] In order to further understand the present invention, the 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel and its preparation method provided by the present invention are described in detail below in conjunction with embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0063] The test standard for tensile strength, yield strength and total elongation in the embodiment of the present invention is GB / T228.1-2010, the gauge length of the tensile specimen is 50 mm, and the tensile rate is 2 mm / min;

[0064] The bending angle corresponding to the maximum load of VDA238-100 three-point bending in the embodiment of the present invention is measured according to the VDA 238-100 three-point bending test standard formulated by the German Association of the Automotive Industry;

[0065] Four-point bending hydrogen embrittlement fracture time: a rectangular specimen of 15×115mm is obtained from the steel plate, and the length direction of the specimen is perpendicular to the rolling direction of the steel plate; a typical specimen is selected for tensile performance testing on a tensile testing machine to obtain the yield strength of the material in the hot stamping + baking state; the specimen is prestressed by a four-point bending fixture. For hot stamping steel, it is difficult for the material to deform or slightly deform under service conditions. Therefore, the prestress σ is generally selected as a percentage of the yield strength, and the maximum does not exceed 1.1 times the yield strength; the loaded specimen is immersed in a solution, which is a 0.1mol / L (pH=1) hydrochloric acid solution, and a camera is used to accurately record the entire process of the specimen and determine the cracking time; during the immersion process, the pH value is tested and adjusted every 24 hours to ensure that the pH value is always 1±0.2. There are 3~5 parallel specimens in each group of stress levels. If one cracked specimen appears, it is determined to be cracked and the corresponding time is recorded. The stress level of this patent is selected as 100% yield strength.

[0066] Example 1

[0067] In this embodiment, the short process preparation method of 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel is carried out according to the following steps:

[0068] 1) Molten steel is melted according to the set composition. The chemical composition mass percentage range of hot-formed steel is: 0.06% C, 1.0% Mn, 0.3% Si, 0.25% Al, 0.028% Ti, 0.25% (Nb + V + Mo), 3.0% Cr, 0.005% (La + Ce), 0.0081% N, 0.0045% P, 0.0015% O, and the remaining elements are Fe and unavoidable impurities;

[0069] During the smelting process, a low-Ca+low-Al magnesium-based composite deoxidizing alloy is used for steelmaking deoxidation. The chemical composition of the deoxidizing alloy is calculated by mass percentage, including: 60% Mg, 20% Al, 16.4% Ca, 3.6% Ba; the deoxidizing alloy is first prepared into alloy particles with a particle size of about 70 mm, and a cored wire (deoxidizing alloy in the core) of 3.3 kg / t Fe is added into the molten steel 28 seconds after the molten steel is tapped to deoxidize the molten steel and modify the inclusions;

[0070] 2) Control the temperature of the molten steel in the ladle to 1612℃, pour the molten steel into the tundish; control the superheat of the molten steel in the tundish to 50℃, and then flow the molten steel from the tundish into the flow ladle; finally, the molten steel flows from the flow ladle into the twin-roll thin strip continuous casting equipment, control the superheat of the molten steel on the upper surface of the molten pool between the casting rolls to 10℃, and obtain a cast strip with a thickness of 1.9mm and a width of 1.2m through casting and rolling under nitrogen protective atmosphere;

[0071] 3) After cooling the cast strip to the start rolling temperature, hot rolling is performed in one pass, the start rolling temperature is 1050°C, the final rolling temperature is 950°C, and the thickness of the obtained hot rolled plate is 1.4 mm;

[0072] 4) cooling the hot-rolled plate obtained above to 560° C. at 10° C. / s through a laminar cooling system after exiting the hot rolling mill, and coiling the plate to obtain a hot-rolled plate after coiling, wherein the oxide layer thickness of the hot-rolled plate after coiling is 5 μm;

[0073] The microstructure of the hot-rolled plate after coiling is composed of ferrite, martensite and bainite, wherein the volume fraction of ferrite is 50%, the volume fraction of martensite is 20%, and the volume fraction of bainite is 30%; and the yield strength of the hot-rolled plate after coiling is 530 MPa, the tensile strength is 690 MPa, and the total elongation is 22%;

[0074] 5) The hot-rolled plate after coiling is first pickled and then processed on the EPS production line to remove the iron oxide scale: the pickling solution is a hydrochloric acid solution, which passes through three pickling tanks with different concentrations of hydrochloric acid in sequence, and the corresponding hydrochloric acid concentrations are 30g / L, 50g / L and 80g / L respectively; the pickling temperature is adjusted to 60℃, and the pickling speed is 60m / min; the EPS production line treatment uses recycled harmless medium water and steel grit to remove the surface oxide scale and achieve rust prevention;

[0075] 6) Hot stamping process: The hot rolled sheet treated with iron oxide is heated to 930℃ for austenitization and kept warm for a certain period of time, with a total heating time of 230s, and then transferred to the die for quenching to 100℃, pressure of 10MPa, holding time of 5s, and transfer time of 5s; the furnace used for heating is a box-type furnace, the atmosphere of the furnace is dry compressed air, and the dew point is controlled at -30℃;

[0076] Through the hot stamping process, a 1000MPa-grade coating-free hot-formed steel is obtained after in-die quenching, and its tensile strength is 1200MPa, the yield strength is 980MPa, the total elongation is 8%, and the corresponding bending angle under the maximum load of VDA238-100 three-point bending is 100° (the thickness of the sheet is 1.4mm); the oxide layer thickness of the 1000MPa-grade coating-free hot-formed steel after in-die quenching is 10nm; the microstructure of the 1000MPa-grade coating-free hot-formed steel after in-die quenching is martensite+bainite+microalloy carbide+ε / η carbide, wherein the volume fraction of martensite is 65%, the volume fraction of bainite is 30%, the volume fraction of microalloy carbide is 0.5%, and the volume fraction of ε / η carbide is 4.5%;

[0077] 7) Baking and coating treatment: After in-mold quenching, the 1000MPa-grade coating-free hot-formed steel is tempered at 170°C for 20 minutes to obtain a baking and coating-treated 1000MPa-grade hydrogen-induced delayed cracking-resistant coating-free hot-formed steel;

[0078] The tensile strength of the 1000MPa grade hydrogen-induced delayed cracking resistant uncoated hot-formed steel treated with baking coating is 1180MPa, the yield strength is 1000MPa, the total elongation is 10%, and the corresponding bending angle under the maximum load of VDA238-100 three-point bending is 110° (for a sheet with a thickness of 1.4mm); in the four-point bending hydrogen embrittlement test, no fracture occurs in HCl with a pH of 1 for 600h;

[0079] The microstructure of the prepared 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel treated with baking coating is martensite + bainite + microalloy carbide + ε / η carbide, in which the volume fraction of martensite is 64%, the volume fraction of bainite is 29%, the volume fraction of microalloy carbide is 0.4%, and the volume fraction of ε / η carbide is 6.6%.

[0080] Example 2

[0081] In this embodiment, the short process preparation method of 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel is carried out according to the following steps:

[0082] 1) Molten steel is melted according to the set composition. The chemical composition mass percentage range of hot-formed steel is: 0.08% C, 0.5% Mn, 1.5% Si, 0.1% Al, 0.012% Ti, 0.03% Nb, 1.5% Cr, 0.05% (La + Ce), 0.0035% N, 0.0055% P, 0.0018% O, and the remaining elements are Fe and unavoidable impurities;

[0083] During the smelting process, a low-Ca+low-Al magnesium-based composite deoxidizing alloy is used for steelmaking and deoxidation. The chemical composition of the deoxidizing alloy is calculated by mass percentage, including: 52.7% Mg, 25% Al, 20% Ca, 2.3% Ba; the deoxidizing alloy is first prepared into alloy particles with a particle size of about 80 mm, and a cored wire (deoxidizing alloy in the core) of 3.5 kg / t Fe is added into the molten steel at 32 seconds after the molten steel is tapped to deoxidize the molten steel and modify the inclusions;

[0084] 2) Control the temperature of the molten steel in the ladle to 1620°C, pour the molten steel into the tundish; control the superheat of the molten steel in the tundish to 70°C, and then flow the molten steel from the tundish into the flow ladle; finally, the molten steel flows from the flow ladle into the twin-roll thin strip continuous casting equipment, control the superheat of the molten steel on the upper surface of the molten pool between the casting rolls to 40°C, and obtain a cast strip with a thickness of 2.1 mm and a width of 1 m through casting and rolling under nitrogen protective atmosphere;

[0085] 3) After cooling the cast strip to the start rolling temperature, hot rolling is performed in one pass, the start rolling temperature is 1000°C, the final rolling temperature is 920°C, and the thickness of the obtained hot rolled plate is 1.4 mm;

[0086] 4) cooling the hot-rolled plate obtained above to 620° C. at 15° C. / s through a laminar cooling system after exiting the hot rolling mill, and coiling the plate to obtain a hot-rolled plate after coiling, wherein the oxide layer thickness of the hot-rolled plate after coiling is 9 μm;

[0087] The microstructure of the hot-rolled plate after coiling is composed of ferrite, martensite and bainite, wherein the volume fraction of ferrite is 55%, the volume fraction of martensite is 15%, and the volume fraction of bainite is 30%; and the yield strength of the hot-rolled plate after coiling is 500 MPa, the tensile strength is 660 MPa, and the total elongation is 25%;

[0088] 5) The hot-rolled plate after coiling is first pickled and then processed on the EPS production line to remove the iron oxide scale: the pickling solution is a hydrochloric acid solution, which passes through three pickling tanks with different concentrations of hydrochloric acid in sequence, and the corresponding hydrochloric acid concentrations are 40g / L, 60g / L and 90g / L respectively; the pickling temperature is adjusted to 70℃, and the pickling speed is 80m / min; the EPS production line treatment uses recycled harmless medium water and steel grit to remove the surface oxide scale and achieve rust prevention;

[0089] 6) Hot stamping process: The hot rolled sheet treated with iron oxide is heated to 900℃ for austenitization and kept warm for a certain period of time, with a total heating time of 250s, and then transferred to the die for quenching to 200℃, pressure 20MPa, holding time of 15s, and transfer time of 10s. During heating, the furnace uses a roller hearth furnace, the furnace atmosphere is dry compressed air, and the dew point is controlled at -5℃;

[0090] Through the hot stamping process, a 1000MPa-grade coating-free hot-formed steel is obtained after in-die quenching, and its tensile strength is 1000MPa, the yield strength is 750MPa, the total elongation is 11%, and the corresponding bending angle under the maximum load of VDA238-100 three-point bending is 130° (the thickness of the sheet is 1.4mm); the oxide layer thickness of the 1000MPa-grade coating-free hot-formed steel after in-die quenching is 30nm; the microstructure of the 1000MPa-grade coating-free hot-formed steel after in-die quenching is martensite+bainite+microalloy carbide+ε / η carbide, wherein the volume fraction of martensite is 95%, the volume fraction of bainite is 2%, the volume fraction of microalloy carbide is 0.2%, and the volume fraction of ε / η carbide is 2.8%;

[0091] 7) Baking and coating treatment: After in-mold quenching, the 1000MPa-grade coating-free hot-formed steel is tempered at 170°C for 20 minutes to obtain a baking and coating-treated 1000MPa-grade hydrogen-induced delayed cracking-resistant coating-free hot-formed steel;

[0092] The tensile strength of the 1000MPa grade hydrogen-induced delayed cracking resistant uncoated hot-formed steel treated with baking coating is 920MPa, the yield strength is 870MPa, the total elongation is 13%, and the corresponding bending angle under the maximum load of VDA238-100 three-point bending is 140° (for a sheet with a thickness of 1.4mm); in the four-point bending hydrogen embrittlement test, no fracture occurs in HCl with a pH of 1 for 600h;

[0093] The microstructure of the prepared 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel treated with baking coating is martensite + bainite + microalloy carbide + ε / η carbide, in which the volume fraction of martensite is 94%, the volume fraction of bainite is 1%, the volume fraction of microalloy carbide is 0.1%, and the volume fraction of ε / η carbide is 4.9%.

[0094] Example 3

[0095] In this embodiment, the short process preparation method of 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel is carried out according to the following steps:

[0096] 1) Molten steel is melted according to the set composition. The chemical composition mass percentage range of hot-formed steel is: 0.06% C, 0.7% Mn, 1% Si, 0.08% Al, 0.02% Ti, 0.20% (Nb + V), 2% Cr, 0.025% (La + Ce), 0.0058% N, 0.0025% P, 0.0022% O, and the rest is Fe and unavoidable impurities;

[0097] During the smelting process, a low-Ca+low-Al magnesium-based composite deoxidizing alloy is used for steelmaking deoxidation. The chemical composition of the deoxidizing alloy is calculated by mass percentage, including: 57% Mg, 25% Al, 15% Ca, 3% Ba; the deoxidizing alloy is first prepared into alloy particles with a particle size of about 75 mm, and a cored wire (deoxidizing alloy in the core) of 3.4 kg / t Fe is added into the molten steel 30 seconds after the molten steel is tapped to deoxidize the molten steel and modify the inclusions;

[0098] 2) Control the temperature of the molten steel in the ladle to 1615℃, pour the molten steel into the tundish; control the superheat of the molten steel in the tundish to 60℃, and then flow the molten steel from the tundish into the flow ladle; finally, the molten steel flows from the flow ladle into the twin-roll thin strip continuous casting equipment, control the superheat of the molten steel on the upper surface of the molten pool between the casting rolls to 30℃, and obtain a cast strip with a thickness of 2.0mm and a width of 1.1m through casting and rolling under nitrogen protective atmosphere;

[0099] 3) After cooling the cast strip to the start rolling temperature, hot rolling is performed in one pass, the start rolling temperature is 1020°C, the final rolling temperature is 940°C, and the thickness of the obtained hot rolled plate is 1.4 mm;

[0100] 4) cooling the hot-rolled plate obtained above to 600° C. at 13° C. / s through a laminar cooling system after exiting the hot rolling mill, and coiling the plate to obtain a hot-rolled plate after coiling, wherein the oxide layer thickness of the hot-rolled plate after coiling is 7 μm;

[0101] The microstructure of the hot-rolled plate after coiling is composed of ferrite, martensite and bainite, wherein the volume fraction of ferrite is 53%, the volume fraction of martensite is 30%, and the volume fraction of bainite is 17%; and the yield strength of the hot-rolled plate after coiling is 520 MPa, the tensile strength is 680 MPa, and the total elongation is 24%;

[0102] 5) After coiling, the hot-rolled plate is first pickled and then processed on the EPS production line to remove the iron oxide scale: the pickling solution is a hydrochloric acid solution, which passes through three pickling tanks with different hydrochloric acid concentrations in sequence, and the corresponding hydrochloric acid concentrations are 35g / L, 55g / L and 85g / L respectively; the pickling temperature is adjusted to 65℃, and the pickling speed is 70m / min; the EPS production line treatment uses recycled harmless medium water and steel grit to remove surface oxide scale and achieve rust prevention.

[0103] 6) Hot stamping process: The hot rolled sheet treated with iron oxide is heated to 920℃ for austenitization and kept warm for a certain period of time, with a total heating time of 240s, and then transferred to the die for quenching to 150℃, pressure of 15MPa, holding time of 10s, and transfer time of 8s; the furnace used for heating is an induction furnace, the atmosphere of the furnace is dry compressed air, and the dew point is controlled at -25℃;

[0104] Through the hot stamping process, a 1000MPa-grade coating-free hot-formed steel is obtained after in-die quenching, and its tensile strength is 1100MPa, the yield strength is 890MPa, the total elongation is 10%, and the corresponding bending angle under the maximum load of VDA238-100 three-point bending is 120° (the thickness of the sheet is 1.4mm); the oxide layer thickness of the 1000MPa-grade coating-free hot-formed steel after in-die quenching is 20nm; the microstructure of the 1000MPa-grade coating-free hot-formed steel after in-die quenching is martensite+bainite+microalloy carbide+ε / η carbide, wherein the volume fraction of martensite is 80%, the volume fraction of bainite is 16%, the volume fraction of microalloy carbide is 0.5%, and the volume fraction of ε / η carbide is 3.5%;

[0105] 7) Baking and coating treatment: After in-mold quenching, the 1000MPa-grade coating-free hot-formed steel is tempered at 170°C for 20 minutes to obtain a baking and coating-treated 1000MPa-grade hydrogen-induced delayed cracking-resistant coating-free hot-formed steel;

[0106] The tensile strength of the 1000MPa grade hydrogen-induced delayed cracking resistant uncoated hot-formed steel treated with baking coating is 1000MPa, the yield strength is 920MPa, the total elongation is 11%, and the corresponding bending angle under the maximum load of VDA238-100 three-point bending is 135° (for a sheet with a thickness of 1.4mm); in the four-point bending hydrogen embrittlement test, no fracture occurs in HCl with a pH of 1 for 600h;

[0107] The microstructure of the prepared 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel treated with baking coating is martensite + bainite + microalloy carbide + ε / η carbide, in which the volume fraction of martensite is 79%, the volume fraction of bainite is 15%, the volume fraction of microalloy carbide is 0.4%, and the volume fraction of ε / η carbide is 5.6%.

[0108] Comparative Example 1

[0109] The preparation method is the same as that of Example 1, except that: C 0.12%, Mn 1.1%, Si 0.1%, Al 0.9%, Ti 0.03%, Cr 1.0%, B 0.003%, and the balance is Fe;

[0110] The tensile strength of the hot-formed steel obtained after in-die quenching in the hot stamping process is 1221MPa, the yield strength is 930MPa, the total elongation is 5.8%, and the corresponding bending angle under the maximum load of VDA238-100 three-point bending is 75° (sheet metal thickness is 1.4mm). It cannot resist high-temperature oxidation during hot stamping, and a micron-level oxide layer will be produced after hot stamping.

[0111] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0112] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel, comprising, by mass percentage: C 0.06~0.08%, Mn 0.5%~1.0%, Si 0.3%~1.5%, Al 0.08%~0.25%, Ti 0.012%~0.028%, (Nb+V+Mo) 0.03%~0.25%, Cr 1.5%~3.0%, (La+Ce) 0.005%~0.05%, N 0.0035%~0.0081%, P≤0.0075%, O<0.0025%, and Mn+Si≤2.0%, 0.4%≤Al+Si≤1.6%, 1.8%≤Si+Cr≤3.3%, and the rest is Fe.

2. The hot-formed steel according to claim 1, characterized in that: The Mn content is 0.7-0.9%.

3. The hot-formed steel according to claim 1, characterized in that: The content of Mn+Si is 1.3%~1.7%.

4. The hot-formed steel according to claim 1, characterized in that: 0.8%≤Al+Si≤1.5%.

5. The hot-formed steel according to claim 1, characterized in that: The Si content is 0.5~1.2%, the Al content is 0.09~0.20%, the Ti content is 0.02~0.026%, (Nb+V+Mo) 0.05%~0.20%, Cr 2.0%~2.8%, (La+Ce) 0.010%~0.025%, N 0.0038%~0.0058%, 2.0%≤Si+Cr≤3.0%.

6. The method for preparing the hot-formed steel according to claim 1, comprising the following steps: S1) preparing the raw materials according to the composition ratio, smelting the obtained mixed raw materials to obtain molten steel; during the smelting process, a magnesium-based alloy is used for deoxidation, and the magnesium-based alloy includes 50-60wt% Mg, 20-25wt% Al, 15-20wt% Ca, and 2.3-3.6wt% Ba; S2) pouring the molten steel into a tundish and a flow ladle in sequence and then into a twin-roller thin strip continuous casting device for continuous casting to obtain a cast strip; S3) cooling the cast strip and then hot rolling it once, laminar cooling the obtained hot-rolled plate and then coiling it to obtain the coiled hot-rolled plate; S4) removing the iron oxide scale from the coiled hot-rolled sheet and then hot stamping the sheet to obtain 1000 MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel.

7. The preparation method according to claim 6, characterized in that: In step S1), the magnesium-based alloy is added in the form of iron cored wire, the addition time is 28-32 seconds after the molten steel is tapped, and the amount of the iron cored wire added is 3.3-3.5 kg / t; In step S2), the temperature of the molten steel is 1612-1620°C; the superheat of the molten steel in the tundish is 50-70°C, the superheat of the molten steel on the upper surface of the molten pool between the casting rollers in the twin-roll thin strip continuous casting equipment is 10-40°C, the continuous casting is carried out under a protective atmosphere, the thickness of the cast strip is 1.9-2.1 mm, and the width is 1-1.2 m.

8. The preparation method according to claim 6, characterized in that: In step S3), the hot rolling start temperature is 1000-1050°C, the final rolling temperature is 920-950°C, the thickness of the hot rolled plate is 1.0-1.7 mm; the laminar cooling rate is 10-15°C / s, the temperature is 560-620°C; the oxide layer thickness of the hot rolled plate after coiling is 5-9 μm; In step S4), the method of removing the iron oxide scale is selected from one or both of pickling treatment and EPS production line treatment; the pickling passes through three pickling tanks in sequence, the acid concentrations are 30-40g / L, 50-60g / L, and 80-90g / L respectively, the pickling temperature is 60-70°C, and the pickling speed is 60-80m / min; the EPS production line treatment is carried out using recycled harmless medium water and steel grit.

9. The preparation method according to claim 6, characterized in that: In step S4), the hot stamping is specifically: The hot rolled plate after removing the iron oxide scale is heated to 900-930°C in a heating furnace, and the total time = (the thickness of the hot rolled plate after removing the iron oxide scale * 100 + 70-90) s, and then transferred to the mold in 5-10s and quenched to 100-200°C, the pressure is 10-20MPa, and the pressure is maintained for 5-15s; the atmosphere of the heating furnace is dry compressed air, nitrogen or argon, and the dew point is -30--5°C; The oxide layer thickness of the 1000MPa grade hydrogen-induced delayed cracking resistant coating-free hot-formed steel is 10-30nm.

10. The preparation method according to any one of claims 6 to 9, characterized in that: The hot stamping further includes tempering, wherein the tempering temperature is 150-200° C. and the time is 10-30 minutes.